Front Cover: H‐Bonded Counterion‐Directed Catalysis: Enantioselective Gold(I)‐Catalyzed Addition to 2‐Alkynyl Enones as a Case Study (Eur. J. Org. Chem. 42/2022). Issue 42 (26th October 2022) - Martí, Àlex; Montesinos‐Magraner, Marc; Echavarren, Antonio M.; Franchino, Allegra
Abstract : The Front Cover illustrates the ability of the squaramide group to remove a chiral anionic ligand from Au(I) by H‐bonding interactions, by analogy with a magnet that attracts a metallic sphere. H‐bonded counterion‐directed catalysis was used to perform an enantioselective tandem cycloisomerization‐nucleophile addition to 2‐alkynyl enones. More information can be found in the Research Article by A. M. Echavarren, A. Franchino et al .